Procedure of developing more energy efficient and electrified hydraulic systems for loader cranes - Rankka, Amy; Dell’Amico, Alessandro (Frontiers in Mechanical Engineering, 2024)
This work presents a process for the requirement management and conceptual design phases of hydraulic systems. The aim is to provide a foundation for developing more energy efficient systems for the working hydraulics of construction machines. A framework is developed and applied in a case study of a loader crane. An important part of the framework is to evaluate and compare different designs based on customer usage of the machine. Emphasis has also been put on incorporating the knowledge and experience of both industry and academia. A large number of different designs are evaluated during a concept exploration phase. The design space is then narrowed down to the system design analysis phase. Losses from simultaneous operation are significant, systems with two and four pumps respectively are therefore selected for analysis by demonstrators. In order to reach equal energy performance, two-pump systems need to be more complex, i.e., they require a more sophisticated control and more components, than four-pump systems. When comparing demonstrator results, the conclusion is that for two-pump systems, it is more challenging to reach the theoretical performance, both in terms of energy efficiency and of drivability, than for the less complex systems made possible with four-pumps.